NZEB target for existing buildings: case study of historical educational building in Mediterranean climate. (December 2017) - Ascione, Fabrizio; De Masi, Rosa Francesca; de Rossi, Filippo; Ruggiero, Silvia; Vanoli, Giuseppe Peter
Abstract: A key element of the Energy Performance of Building Directive 2010/31/EU is the introduction of nearly zero energy building (NZEB) standard for new constructions. However, considering the very low rate of new built volume, the major change for achieve the sustainable grow of the European economy, appears to be the renovation of existing building stock. But, is it possible to reach very low or nearly zero energy standard during refurbishment design? Proposed paper tries to answer this question, evaluating if the refurbishment of historic architectures to very low energy need is possible and economically feasible. With reference to a case study, this paper investigates the cost-optimal energy refurbishment of a Renaissance-style palace, located in the center of Naples, South Italy. The adopted methodology consists of various steps. Firstly, a model of the building has been accurately built and calibrated. Then, it has been used to evaluate possible interventions concerning both the envelope and the energy systems. The best solutions, chosen according to the European methodology of cost-optimality, have been combined in a last simulation. The results show that great energy savings as well as economic and environmental improvements are possible, although heritage buildings present a less flexibility in the proposal of energy efficiency measures.